SEKOLAH PANTAI AS THE EXPOSURE OF CREATING HOLISTIC FUN ENGLISH EXPERIENCE IN PACITAN EAST JAVA - Chusna Apriyanti (UAD TEFL International Conference)
This paper aims to know the implementation of fun English learning through Sekolah Pantai in Pacitan East Java and the obstacles in implementing fun English learning to the children. The vision of this program is for every child in Indonesia has the opportunity to learn, to have healthy start, and to feel supported and secure living in a clean environment that is prepared for natural disasters. The researcher uses descriptive qualitative research design. The data are collected through observation and interview to the children and the volunteers of Sekolah Pantai. The result shows that all of the programs use English language with small portion of Indonesian language completed with theoretical input, group work as well as active sports games or garden work. English is included implicitly in four basic activities: ocean conservation, open class for kids, environmental workshop day with eco-ambassadors from high schools, and supporting local teachers through seminar and workshop to create fun English learning at schools. The volunteers use methods of teaching through arts, music, dance, storytelling, and other ways to share knowledge and integrate soft skills into the practical learning. However, there are some obstacles appeared during the program, such as: the children’ anxiety in communicating using English language, distrust from the public schools that need effort to make them believe to the programs, distrust from the society because of the native speakers volunteer, time management in conducting parallel activity for the students in private schools.